T-Public application / Nurul Nadhirah Mohd Anuar, Ahmad Danial Ahmad Darimi … [et al.] - Mohd Anuar, Nurul Nadhirah; Ahmad Darimi, Ahmad Danial; W.Kamarudin, Wan Nur Hamizah (2018)
T-Public is filled with artworks to be sale and also T-Public also provide an editor program for graphic editor choice of fonts and colors, custom filters and various Tshirt style templates to inspire your creativity. Once designer and customers done designing your one-of-a-kind T-shirt, easily share your design with friends over social media or better yet, invite them to follow you in T-Public and start building each other's profile. The innovative of collecting the local designers artworks also great for collaborations.